2023
DOI: 10.3390/md21040206
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Common Octopus (Octopus vulgaris) Ink Proteome and Bioactive Peptides Using Proteomic Approaches

Abstract: The common octopus (Octopus vulgaris) is nowadays the most demanded cephalopod species for human consumption. This species was also postulated for aquaculture diversification to supply its increasing demand in the market worldwide, which only relies on continuously declining field captures. In addition, they serve as model species for biomedical and behavioral studies. Body parts of marine species are usually removed before reaching the final consumer as by-products in order to improve preservation, reduce shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Within the Mollusca, cephalopods are promising targets for bioprospecting. Distinct omics studies in Octopus vulgaris identified candidate proteins and peptides for biotechnological applications in the mucus produced by the skin and in the ink as well, namely molecules that might have antimicrobial, antitumoral, antiviral activities (among others), or even be used as potential immune stimulators (Imran et al, 2023;Peŕez-Polo et al, 2023). These studies applied a similar methodology to identified peptides and proteins of interest by employing a shotgun proteomic strategy coupled with GO, pathway and network analyses.…”
Section: Omics Studies Employed To Unravel Promising Bioactivesmentioning
confidence: 99%
“…Within the Mollusca, cephalopods are promising targets for bioprospecting. Distinct omics studies in Octopus vulgaris identified candidate proteins and peptides for biotechnological applications in the mucus produced by the skin and in the ink as well, namely molecules that might have antimicrobial, antitumoral, antiviral activities (among others), or even be used as potential immune stimulators (Imran et al, 2023;Peŕez-Polo et al, 2023). These studies applied a similar methodology to identified peptides and proteins of interest by employing a shotgun proteomic strategy coupled with GO, pathway and network analyses.…”
Section: Omics Studies Employed To Unravel Promising Bioactivesmentioning
confidence: 99%